Negative campaigns, interpersonal trust, and prosocial behavior: The mediating effect of democratic experience. (February 2020) - Haas, Nicholas; Hassan, Mazen; Morton, Rebecca
Abstract: Previous studies of negative election campaigns have not addressed the possible effects of campaign environments on interpersonal trust and prosocial behavior between voters. We provide the first evidence of these effects through an incentivized lab experiment conducted among student subjects in Egypt in 2014 and in the United States in between 2016 and 2018. This comparison allows us to tease out the mediating effect of subjects' prior experience with competitive elections. In our Egypt experiment, trust in other voters significantly decreased (by 15%) when voters were primed with a negative personality campaign as compared to a neutral baseline. Interpersonal trust also decreased in negative policy campaigns (by 8%). Among US subjects however, such effects do not materialize. Our explanation of these divergent outcomes is that the priming effect of negative election campaigns on interpersonal trust takes place when the experience of competitive elections is still quite new.